Influence of graphene addition in epoxy resin applied to carbon fiber structural reinforcement of concrete beams - Abrahão, Taila Brandes; Coladetti, Virgínia Turatti; Medeiros, Arthur; Kloss, Juliana Regina; Mazer, Wellington (Periódicos Brasil. Pesquisa Científica, 2026)
Structural reinforcement plays a key role in preserving and adapting structures that are nearing the end of their useful life, that were built according to obsolete standards, or that need to be adapted for new uses beyond their original capacities. The use of carbon fiber reinforced polymers (CFRP) stands out for this function, as it has good mechanical and corrosion resistance, low density, and minimal alteration in the geometry of the reinforced element. However, premature detachment of CFRP, resulting from adhesive characteristics such as brittle fracture mode and low fracture toughness, can compromise the structural stability of the system. In connection with this, recent research has focused on improving polymer matrices by incorporating nanomaterials, such as graphene, which provides greater toughness and mechanical strength to the composite when properly dispersed. Based on this, the objective of this study was to evaluate the influence of adding graphene to epoxy resin applied to carbon fiber structural reinforcements in concrete beams. The composite was produced by incorporating graphene into the epoxy resin, using a torque rheometer for dispersion; its functional groups, thermal, and mechanical properties were analyzed by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TG/DTA), and tensile test. The beams were subjected to a four-point bending test, in which data were obtained on the stress at the appearance of the first crack, breaking stress, and evaluation of the failure mode of the samples. The experimental data showed that the compositions with graphene had a greater deformation capacity before failure. However, the cracking and rupture stresses of the beams reinforced with the epoxy/graphene composite and with the pure resin were statistically equal. As this result is linked to the failure mode, there remains the possibility that graphene contributes to improving structural reinforcement, especially in increasing toughness - the ability to absorb energy before rupture.